SOCIO-GEOGRAPHICAL DIRECTIONS AND STAGES OF ETHNOECOLOGICAL RESEARCH (Scientific journal of the Fergana State University, 2024)
In the article, ethnoecological culture as an integral part of general culture is widely studied in the fields of cultural studies and ethnoculture. Ethnoecological studies of the geographical direction are aimed at studying the relationship of ethnic groups with the natural environment through their conscious activities. The analysis of ethnoecological culture and its components as the main object, which is the main object of ethnoecological research in the field of geography, which is the result of such systemic relationships, is considered in detail. The article also analyzes in detail the directions and sections of ethno-ecological culture.